Prevalence of Inherited Ichthyosis in Romania. (2015) - Maier, Dalila; Moica, Sorina; Moica, Theodor; Cosgarea, Rodica
Abstract: Inherited ichthyosis in Romania constitutes a health problem of unknown dimension. Over a period of nine months we collected information about inherited ichthyosis patients from three different sources. We found 124 of individuals in 32 counties and Bucharest, the majority of cases being reported by the social assistance services. We characterized our population by gender, age and domicile area and we compared the number of the identified inherited ichthyosis cases to the local stable population data from 2011 Romanian census in each domicile area. The prevalence of inherited ichthyosis cases was calculated for each source of information and in addition we calculated the cumulated prevalence of medical and social source and total prevalence of all three sources, always reporting to the stable population of the domicile county of reported patients. Statistical analyses and interpretation of data for comparing these values of prevalence were used to determine if the prevalence is different in these sources. We realized first a study to evaluate the existence of significant statistic difference between mean values of prevalence in each source type and subsequently we compared how addition of new data to the main source modified its prevalence. We found that the information collected from local counties official organisms for social assistance and protection is the most significant for the final results and this information is different from that of medical sources and other nonconventional sources.